Violations of basic rights of prisoners in conventional and Islamic law: theory and practice - Ali, Mohammed Farid; U Tun Aung, Maulana Akbar Shah; Kuttiyani Muhammad, Muneer (IIUM Press, International Islamic University Malaysia, 2019)
In prisons, the convicted are most often unattended by the authority and therefore they become victim to abuses and maltreatment. Their basic rights as humans are being violated in most of the prisons. Although there have been a lot of laws and regulations upholding the rights of prisoners prevalent in the international community, it seems ineffective in protecting their rights in real life. This paper examines the problems of the prisoners in general and discloses the issue of human rights violation of prisoners. The paper particularly exposes problems in the prisons such as sexual abuse, mental and physical torturing, illegal enforcement of prison labour, overcrowding, poor education and health care initiations. With approaching the issues of the prisoners from a human rights perspective, the paper also explores the issues from an Islamic law viewpoint and attempts to provide a conceptual frame work of solutions. A critical and descriptive analytical approach is employed in this study.